Implementing a REBOA Program Outside Large Academic Trauma Centers: Initial Case Series and Lessons Learned at a Busy Community Trauma Program - Glaser, Jacob; Czerwinski, Adam; Alley, Ashley; Keyes, Michael; Piacentino, Valentino; Pepe, Antonio (Journal of Endovascular Resuscitation and Trauma Management, 2018)
Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) has become an established adjunct to hemorrhage control. Prospective data sets are being collected, primarily from large high-volume trauma centers. There are limited data and guidelines, to direct the implementation and use of REBOA outside these highly resourced environments. Smaller centers interested in adopting a REBOA program could benefit from closing this knowledge gap. Methods: A clinical series of cases utilized REBOA at a busy community trauma center (ACS Level 2) from January 2017 to May 2018. Seven cases are identified and reported, including outcomes. Considerations and ‘lessons learned’ from this early institutional experience are discussed. Results: REBOA was performed by trauma and acute care surgeons for hemorrhage and shock (blunt trauma n = 3, penetrating trauma n = 2, no trauma n = 2). All were placed in Zone 1 (one was placed initially in Zone 3 then advanced). The mean (SD) systolic pressure (mmHg) before REBOA was 43 (30); post-REBOA pressure was 104 (19). Four of the patients were placed via an open approach, and three were percutaneous (n = 2 with ultrasound). All with arrest before placement expired (n = 3) and all others survived. Complications are described. Conclusions: REBOA can be a feasible adjunct for shock treatment in the community hospital environment, with outcomes comparable to large centers, and can be implemented by acute care and trauma surgeons. A rigorous process of improvement programs and critical appraisal are critical in maximizing the benefit in these centers.